Decoupling pressure and distribution effects of flow fields on polymer electrolyte fuel cell system performance. (December 2019) - Heck, Joshua D.; Vaz, Warren S.; Koylu, Umit O.; Leu, Ming C.
Highlights: Discussed impacts of pressure drop on auxiliary system and inlet mixture properties. Showed that pressure effects can have significant impact on fuel cell performance. Proposed a method for decoupling pressure/distribution effects on fuel cell performance. Demonstrated the method of decoupling in comparison of serpentine and parallel designs. Abstract: The performance of Polymer Electrolyte Membrane Fuel Cells (PEMFCs) is highly dependent on the flow distribution and pressure of reactant gases, which are controlled by flow field design. The relative importance of differing supply pressure requirements of flow field designs in PEMFCs is considered here. A First-Law analysis of the auxiliary system is developed in order to demonstrate how the pressure drop affects all auxiliary system components and fuel cell unit performance. A method of comparison is then proposed to eliminate the effects of pressure in the comparison of fuel cells with different flow field designs. This method is applied to the single serpentine and parallel designs by Computational Fluid Dynamics (CFD) simulation. It is shown that, of the serpentine design's 17.1% better performance, mass transport effects provide 12.2% improvement, and pressure effects account for the remaining 4.9%. Finally, a metric is proposed by which the relative effect of pressure between different flow field designs may be estimated for past results not using the recommended method, and is demonstrated by application to results found in existing literature.